First Evidence that Hatchlings of Chelonia mydas Emit Sounds - Ferrara, Camila Rudge; Mortimer, Jeanne A.; Vogt, Richard Carl (Copeia, 2014)
Hatchling green turtles (Chelonia mydas) were recorded emitting sounds at Ascension Island, South Atlantic Ocean, on 19 May 1978. Analysis revealed that the 70 sounds recorded could be separated into four sound categories. The sounds were complex and characteristic of a contact call, and were similar to those recently reported in other species of aquatic turtles. The relationship between the structure and frequency of the sounds and levels of predation on turtle eggs and hatchlings, especially by ghost crabs (Ocypode spp.), warrants further study. © 2014 by the American Society of Ichthyologists and Herpetologists.
Keywords: Bioacoustics; Crab; Egg; Hatching; Sound Propagation; Turtle; Vocalization; Young Population; Ascension Island; Chelonia Mydas; Ocypode; Ocypodidae; Testudines